Relationship of fiber intake, consumption of fast food and sugar-sweetened beverages with overweight in students of Pesanggrahan 03 Public Elementary School Jakarta - Kurnia Eka Fadhilah; Izna Nurdianty Muhdar; Fildzah Badzlina (Sarana Ilmu Indonesia (salnesia), 2025)
Overweight is a condition caused by abnormal fat accumulation in adipose tissue that has an impact on body health, such as high cholesterol, hypertension, diabetes mellitus, and heart disease. Fiber intake, fast food consumption, and consumption of sugar-sweetened beverages are factors in eating habits that influence the occurrence of overweight. The problem of overweight in children can continue into adulthood, increasing the risk of disease complications and premature death. This study aims to determine the relationship between fiber intake, fast food consumption, and consumption of sugar-sweetened beverages with overweight in students of SDN Pesanggrahan 03 Jakarta. This study was conducted in February–April 2023. The research method used was quantitative observational with a cross-sectional approach. A total of 115 subjects were selected using a proportional random sampling technique. Data collection on the overweight variable was carried out by measuring body weight and height, data on the fiber intake variable using the Semi Quantitative-Food Frequency Questionnaire (SQ-FFQ), while data on fast food consumption and consumption of sugar-sweetened beverages using the Food Frequency Questionnaire (FFQ). Data were collected univariately and bivariately using the Chi Square test. The study found that 38.3% of subjects were overweight, there was a relationship between fiber intake and consumption of sugar-sweetened beverages with overweight (p<0.05), while fast food consumption had no relationship with overweight (p>0.05).